ANALISIS GAYA MENGAJAR GURU PADAMATA PELAJARAN AKIDAH AKHLAK DI MTs NURUL FURQOON BINJAI - Azzahra, Wida (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2022)
This paper is entitled Analysis of Teacher's Teaching Style on Akidah Akhlak Subject at MTs Nurul Furqoon Binjai. 2021/2022. (2) To find out the obstacles faced by teachers in applying teaching styles to Akidah Akhlak subjects at MTs Nurul Furqoon Binjai TP. 2021/2022. (3) To find out the solutions made by the teacher in perfecting the teaching style of the Akidah Akhlak subject at MTs Nurul Furqoon Binjai TP. 2021/2022. This type of research is descriptive qualitative research. The subject of this research is the teacher of Akidah Akhlak in grade VII. Data collection techniques used are observation, interviews and documentation. The results showed that: (1) All teaching styles, both classical teaching styles, technological teaching styles, personalized teaching styles and interactional teaching styles have been used, but the most frequently used teaching style is interactional teaching style, because this teaching style is teacher and students play an active role and relate to the facts. (2) Obstacles faced by teachers are obstacles in conveying the material of moral aqidah and having to adjust the material and teaching style. (3) The solution made by the teacher is to take the initiative to master the four teaching styles, then adjust the material and teaching style to be used.